Reviews of environmental contamination and toxicology - Whitacre, David M. (Reviews of Environmental Contamination and Toxicology, Continuation of Residue Reviews, 2012)
CONTENTS Foreword Preface Plastics in the Marine Environment: The Dark Side of a Modern Gift Jort Hammer, Michiel H.S. Kraak, and John R. Parsons Mercury Pollution in Malaysia Parvaneh Hajeb, Jinap Selamat, Ahmad Ismail, Nor Ainy MahyudinGenotoxic and Reprotoxic Effects of Tritium and External Gamma Irradiation on Aquatic Animals Christelle Adam-Guillermin, Sandrine Pereira, Claire Della-Vedova, Tom Hinton, Jacqueline Garnier-Laplace Index